From Culture to Classroom: Study Ethnomathematics in House of Using Banyuwangi - Rachmaniah Mirza Hariastuti; Mega T. Budiarto; Manuharawati Manuharawati (SAINTIS Publishing, 2019)
Banyuwangi is a town part of Java island, Indonesia. Cultural of Banyuwangi still run by original society named Using tribe. One of the culture which still defended by Using tribe is custom house. The paper describe about house of Using Banyuwangi and instructional design that made from the result of explore activity. This research joining ethnography method and development research. While the data collecting done with observation method, interview, and documentation. As for study device developed with ADDIE model that limited at development step. The result showed that house of Using’s construction show the existence of mathematics concepts specially geometry two dimension, pythagoras, and similarity. This result used to developed the instructional design based on contextual teaching – learning. Selected items is pythagoras. The instructional design will be implementing at research hereinafter.